2018
DOI: 10.1097/pr9.0000000000000674
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine for pain management

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 62 publications
(88 reference statements)
1
60
0
7
Order By: Relevance
“…Clinical data are consistent with analgesic benefits of NMDAR antagonists for neuropathic pain 1 , CRPS 1,8 , acute pain in the emergency room 15 , and a reduced requirement for opiods 4 .…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Clinical data are consistent with analgesic benefits of NMDAR antagonists for neuropathic pain 1 , CRPS 1,8 , acute pain in the emergency room 15 , and a reduced requirement for opiods 4 .…”
Section: Introductionmentioning
confidence: 59%
“…across time points or different dosages), all such data were extracted. The following data decisions were also made: (1) for intravenous ketamine studies, only pain outcome data collected during the infusion period were extracted, due to ketamine's rapid elimination from the bloodstream 24 ; (2) When M/SDs were not reported, effect sizes were calculated from any other data that allowed their computation 7 ; (3) for a few studies reporting use of multiple outcomes but only providing data for some outcomes, data were extracted for available outcomes, and; (4) while NMDA dosage in mg/kg bodyweight was extractable for most studies, (i) 16 studies reported total dose only, and (ii) 1 study reported blood plasma. For (i), mg/kg was calculated using mean body weight imputed from study sex composition and country 35 , and for (ii) we used published equivalency data for blood plasma 2,34 .…”
Section: Data Extractionmentioning
confidence: 99%
“…Ketamine at a low dose, has been used as a pharmacological intervention for pain relief in the emergency department during procedural sedation for many years [17]. Low dose ketamine in the emergency department may be especially useful as an intervention for patients with refractory pain due to high tolerance levels to opioid analgesics that may also have multifactorial components such as neuropathic pain, depression and inflammatory processes [7].…”
Section: Indications For Administration Of Low Dose Ketaminementioning
confidence: 99%
“…If low dose ketamine is used in the emergency department as a pharmacological treatment for pain, it is important to take into consideration the risks and benefits, least effective and most effective uses. Low dose ketamine is an effective pharmacological treatment of pain by itself and as an adjunct to opioids [7] [30] because it is a non-competitive NMDA antagonist and it does not interfere with receptors used by opioids [7] [19] [30]. As an adjunct therapy, it is especially important to consider the dosing of opioids in order to prevent opioid-ketamine adverse reactions.…”
Section: Considerations For Practitioners and Nursesmentioning
confidence: 99%
See 1 more Smart Citation